Budaya: Sumber Kekuatan Sekaligus Kelemahan Organisasi - Achmad Sobirin (Jurnal Siasat Bisnis, 2002)
No longer after apprearing in Administrative Science Quarterly in 1979, the term "organizational culture" became a daily language among academicians manager, and business practioners. At that time they perceived that strong culture means good performance. Through the time however they realized that strong culture could also mean liabilties for an organization especially when the culture does not match the environment. That way in developing organizational culkture, adaptability should be taken into consideration so that culture become an asset really.Key Word: Organizational culture, stromg culture, and weak culture.